The Little Data Book 2007 - World Bank (World Development Indicators, 2007)
Now in its eighth edition, this pocketsized reference on key development data for over 200 countries provides profiles of each country with 54 development indicators about people, environment, economy, technology and infrastructure, trade, and finance. It is intended as a quick reference for users of World Development Indicators, WDI Online, and the Atlas of Global Development